Attendance Tracking System for Form 6 - Abd Rahman, Danish Hossman; Mohd Salikon, Mohd Zaki (Applied Information Technology And Computer Science, 2025)
This project develops a specialized Attendance Tracking System using Radio-Frequency Identification (RFID) technology, specifically tailored for Form 6 students at SMK Benut. Addressing the challenges of traditional attendance methods, this system utilizes RFID technology to track student presence during exams in an efficient, accurate, and secure manner. The primary focus is on overcoming inefficiencies such as time consumption, data inaccuracies, and the reduction of potential latecomers or absenteeism prevalent in manual processes. The system design emphasizes user-friendly interfaces for educators and administrators, integrating seamlessly with existing educational infrastructures. Key features include automated attendance recording, real-time data processing, and a centralized database for secure information management. The implementation follows a Prototype Methodology, ensuring adaptability to stakeholder feedback and evolving educational requirements. This initiative is a key step towards improving academic integrity and administrative efficiency in educational institutions, establishing a standard for technology-driven attendance management in academic assessments.